THE PRODUCTION OF VIDEOS IN PRESERVICE TACHER EDUCATION IN DIDATICS OF MATHEMATICS - Brefere Arnoni, Maria Eliza [UNESP]; Scucuglia, Ricardo [UNESP] (Unesp-faculdade Ciencias & Letras, 2017)
In this article, we present a qualitative case study to discuss the creation of digital videos in pre-service mathematics teacher education. The audiovisual production scenario is a course of Didactics of Mathematics and the main subject of students' discussion is the educational activity, with emphasis on the Methodology of Dialectic Mediation (M.M.D.). Undergraduate students created a narrative structure composed of three moments: (1) textual display with musical background on the phases of the educational activity and the stages of M.M.D. (2) presentation of a musical performance created on M.M.D. (3) dialogic / reflective discussion of students about the didactic-pedagogical role of M.M.D. in training and performance of teachers. In our analysis, we highlight the use of the arts and multimodality in the formative process of the three future teachers of mathematics in the digital narrative produced. We believe that the video created has pertinent aspects regarding conceptual sense, emotion and sensation and that the use of digital technologies has great innovative potential in teaching practice. In this respect, it becomes relevant to highlight that the educational process centered on M.M.D. is developed in the education of undergraduate students, regarding the conceptual formation of students of the elementary school.
Keywords: Digital videos; Methodology of Dialectic Mediation; Multimodality